2005
DOI: 10.1111/j.1945-5100.2005.tb00180.x
|View full text |Cite
|
Sign up to set email alerts
|

An appraisal of the Serra da Cangalha impact structure using the Euler deconvolution method

Abstract: Abstract-The applicability of the Euler deconvolution method in imaging impact crater structure vis-à-vis delineation of source depth of the circular magnetic anomaly and/or basement depth beneath the crater is addressed in this paper. The efficacy of the method has been evaluated using the aeromagnetic data obtained over the Serra da Cangalha impact crater, northeastern Brazil. The analyses of the data have provided characteristic Euler deconvolution signatures and structural indices associated with impact cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Sources located outside the collar are spread out along the annular basin, showing the largest calculated depth values in the 500–1500 m range. These results, especially those along the collar of the central uplift, show that the magnetic sources under the central uplift are shallower than suggested by Adepelumi et al. (2005) based on analysis of low‐resolution data.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Sources located outside the collar are spread out along the annular basin, showing the largest calculated depth values in the 500–1500 m range. These results, especially those along the collar of the central uplift, show that the magnetic sources under the central uplift are shallower than suggested by Adepelumi et al. (2005) based on analysis of low‐resolution data.…”
Section: Resultsmentioning
confidence: 55%
“…2010a). According to Adepelumi et al. (2005b), the crystalline basement underneath the structure lies at a depth of 1–1.5 km.…”
Section: Introductionmentioning
confidence: 99%
“…The wider region of the sedimentary basin around Serra da Cangalha appears undeformed, with flat‐lying strata and a morphology dominated by table mountains. Recently, several geophysical studies have been carried out at Serra da Cangalha (Adepelumi et al. 2004, 2005; Abraham et al.…”
Section: Introductionmentioning
confidence: 99%
“…Some geophysical analysis of the structure and modeling of the data has been performed in recent years (Adepelumi et al 2003a(Adepelumi et al , 2003b(Adepelumi et al , 2004(Adepelumi et al , 2005a(Adepelumi et al , 2005b. Interpretation of aeromagnetic data (Adepelumi et al 2003b(Adepelumi et al , 2004) indicated a diameter of 12.7 km for the Serra da Cangalha structure, and the magnetotelluric investigation by Adepelumi et al (2004) resulted in the hypothesis that the likely impact-induced structural deformation below and in the environs of the crater did not exceed a depth of 2 km.…”
Section: Introductionmentioning
confidence: 99%
“…Interpretation of aeromagnetic data (Adepelumi et al 2003b(Adepelumi et al , 2004) indicated a diameter of 12.7 km for the Serra da Cangalha structure, and the magnetotelluric investigation by Adepelumi et al (2004) resulted in the hypothesis that the likely impact-induced structural deformation below and in the environs of the crater did not exceed a depth of 2 km. A 2-D resistivity model (Adepelumi et al 2005a(Adepelumi et al , 2005b) suggested a 4-layer model for the structure: a thin resistive layer underlain by a conductive layer, weathered basement and, ultimately, resistive crystalline basement. The depth to the basement is estimated at 1.1 km.…”
Section: Introductionmentioning
confidence: 99%